2022
DOI: 10.21608/ejhm.2022.256581
|View full text |Cite
|
Sign up to set email alerts
|

Changes In the Menstrual Cycle Among the Covid-19 Vaccinated Women in The Eastern Province of Saudi Arabia: A Cross-Sectional Survey, 2022

Abstract: Background: There is growing concerns that COVID-19 vaccination causes disruption to menstrual cycle. The study has showed that several women required gynecological visits claiming menstrual irregularities or abnormal uterine bleeding after the first and second doses of vaccination (regardless of the type of vaccine used). Objective: This study was conducted in the eastern province of Saudi Arabia to assess the effect of Covid-19 vaccination on the menstrual cycle of the women. Material and methods: It was a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The most astonishing result was a significant increase in cycle length. This was in concordance with what was previously reported by Edelman et al 10 However, in a study conducted on 343 women in Saudi Arabia, 14% of the participants reported an increase in cycle length, whereas 10% had a decrease in length to less than 25 days 18 . This implies that COVID‐19 vaccines can influence the cycle length in a bidirectional way.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most astonishing result was a significant increase in cycle length. This was in concordance with what was previously reported by Edelman et al 10 However, in a study conducted on 343 women in Saudi Arabia, 14% of the participants reported an increase in cycle length, whereas 10% had a decrease in length to less than 25 days 18 . This implies that COVID‐19 vaccines can influence the cycle length in a bidirectional way.…”
Section: Discussionsupporting
confidence: 92%
“…17 However, in a study conducted on 343 women in Saudi Arabia, 14% of the participants reported an increase in cycle length, whereas 10% had a decrease in length to less than 25 days. 18 This implies that COVID-19 vaccines can influence the cycle length in a bidirectional way.…”
Section: Discussionmentioning
confidence: 99%
“…Qashqari et al .,[ 10 ] reported postvaccine menstrual changes in 46.7% of the study participants. In a study by Almousa[ 11 ] involving 343 women, 60.3% of participants reported menstrual irregularities postvaccination, namely disturbances in the duration of the cycle. For about 14% of the participants, the cycles ran longer than 35 days, and for about 10.2% of participants, they were shorter than 25 days.…”
Section: Introductionmentioning
confidence: 99%